Synthesis and Discovery of Ligustrazine–Heterocycle Derivatives as Antitumor Agents - Ma, Shitang; Zhang, Ning; Hou, Jiafu; Liu, Shijuan; Wang, Jiawen; Lu, Baowei; Zhu, Fucheng; Wei, Peipei; Hong, Ge; Liu, Tianjun (Frontiers in Chemistry, 2022)
Ligustrazine (TMP) is a natural pyrazine alkaloid extracted from the roots of Ligusticum chuanxiong hort, and has been proven to be a potential antitumor agent. A series of 33 ligustrazine-heterocyclic (TMPH) derivatives were designed, synthesized, subject to antitumor screening assay, molecular docking and drug-like properties prediction. TMP was firstly spliced with other heterocyclic derivatives and 8-12 methylene alkyl chain as linker, and 33 TMPH derivatives were obtained and structural confirmed by 1H-NMR, 13C-NMR, and high-resolution mass spectra (HR-MS) spectral data. The antiproliferative activities against human breast cancer cell MCF-7, MDA-MB-231, mouse breast cancer cell 4T1, mouse fibroblast L929 and human umbilical vein endothelial cell HUVEC, were evaluated by MTT assay. Among these newly synthetic TMPH compounds, compound 12-9 displayed significant inhibitory activity with IC50 value in low micromolar range (0.84±0.02 µM against MDA-MB-231 cell line). Inspired by these results, the antitumor effects of TMPH 12-9 were further evaluated by plate cloning, Hoechst 333 42 staining, Annexin V-FITC/PI staining. It was demonstrated that TMPH 12-9 could inhibit the proliferation and apoptosis of breast cancer cells at cellular level. Furthermore, molecular docking of the compounds 12-9 into active site of the BCL-2, CASP-3 and PSMB5 target proteins were performed to explore the probable binding mode. Finally, the 33 newly synthesized compounds were predicted to have good drug-like properties in a theoretical study. In conclusion, A series of 33 TMPH derivatives were designed, synthesized, subject to antitumor screening assay, molecular docking and drug-like properties prediction. And TMPH 12-9 displayed potent inhibitory activity of proliferation and apoptosis of breast cancer cells at cellular level. It also suggested that TMPH 12-9 could inhibit proliferation through PSMB5 and apoptosis through BCL-2/CASP-3 apoptotic signaling pathways with good drug-like properties. The above results broaden our thinking for searching for effective bioactive components from Chinese natural medicine, finding key precursor lead derivatives.